An analysis of the dynamic range of Distributed Acoustic Sensing for Earthquake Early Warning - Martijn van den Ende; Alister Trabattoni; Marie Baillet; Diane Rivet (Seismica)
Owing to its deployment and sensing characteristics, Distributed Acoustic Sensing (DAS) has been touted as a promising technology for low-cost and low-latency Earthquake Early Warning (EEW). While preliminary experiments conducted by several research groups have yielded encouraging results, it must be acknowledged that these EEW feasibility studies were performed only on low-magnitude events. When exposed to the wavefield of a large magnitude earthquake (being the prime subject of EEW), the DAS strain rate recordings are likely to become highly distorted ("saturated") due to cycle skipping of the optical phase measurements, to an extent that the recorded data start to degrade to uniform random noise. This clearly poses a major challenge to EEW, as neither amplitude nor phase information can be readily extracted from saturated DAS data. In this study, we perform a detailed analysis of the dynamic range of DAS, both from theoretical and practical perspectives. We offer a set of criteria that need to be met for matching the DAS dynamic range with EEW targets, and we propose a computationally convenient method to quantify the information content of saturated recordings. We apply these methods to DAS data recorded offshore Chile, and identify several avenues for future research to improve the feasibility of DAS for EEW.